Case-based teaching of fatal incidents in outdoor education teacher preparation courses. Issue 3 (3rd July 2017) - North, Chris; Brookes, Andrew
ABSTRACT: This article examines the use of case-based approaches to fatal incidents in outdoor education (OE) with a view to fatality prevention. Fatalities are rare in OE and therefore it is nearly impossible for teachers to learn how to avoid fatalities from their own past experiences. It is, however, possible to learn from the mistakes of others through studying accounts of fatalities. Andrew Brookes, working with specialist OE undergraduates nearing the end of their course, develops the argument for reframing fatality cases as narratives in order for students to not simply analyse the incident in hindsight, but to view the accounts from the perspectives of the people involved at the time. Chris North discusses how he examined the impact of case-based fatality learning on pre-service teachers with a range of outdoor experience levels. The responses of students to studying fatalities required him to reframe his approach and consider how to better differentiate learning. The article argues that case-based learning can make a unique and important contribution to safety, but requires reflexive consideration of both curricular and pedagogical aspects.